Wood Anatomy of Croton L. (Euphorbiaceae) Reflecting Systematic, Ecological and Evolutionary Aspects - Jangid, Prem Prakash; Gupta, Sangeeta (Indian Forester, 2015)
Wood microstructure with systematic, ecological and evolutionary aspects of six species of Croton L. (Euphorbiaceae) from India is described. Wood is diffuse porous, radial multiples of 4 or more common with some short radial multiples and solitary vessels. Perforation plate simple, intervessel pits rounded and alternate. Fibre libriform, non-septate and thin to thick walled. Parenchyma apotracheal, diffuse to diffuse in aggregate and reticulate or narrow banded. Rays heterocellular, containing non-chambered prismatic or rhomboidal crystals and druses. Disjunctive ray parenchyma walls and perforated ray cell observed. C. scabiosus and C. malabaricus show distinctness in some ray and vessel characteristics. Species show adaption to highly mesic condition except C. scabiosus. Few remnants of wood anatomy are evident of both primitive and advance characters in this genus. Systematic wood anatomical survey shows its close relation to subgenus Croton and distance relation to subgenus Moacroton and sister groups of genus Croton, such as, Cubacroton, Brasiliocroton, Acidocroton and Astrea.